Determination of chlorophylls in Taraxacum formosanum by high-performance liquid chromatography-diode array detection-mass spectrometry and preparation by column chromatography - Loh, C. H.; Inbaraj, B. S.; Liu, M. H.; Chen, B. H.
Taraxacum formosanum, a well-known Chinese herb shown to be protective against hepatic cancer as well as liver and lung damage, may be attributed to the presence of abundant carotenoids and chlorophylls. However, the variety and content of chlorophylls remain uncertain. The objectives of this study were to develop an high-performance liquid chromatography? diode array detection?mass spectrometry method for determination of chlorophylls in T. formosanum and preparation by column chromatography. An HyPURITY C18 column and a gradient mobile phase of water (A), methanol (B), acetonitrile (C), and acetone (D)could resolve 10 chlorophylls and an internal standard Fast Green FCF within 30 min with a flow rate at 1 mL/ min and detection at 660 nm. Both chlorophylls a and a? were present in the largest amount (1389.6 ?g/g), followed by chlorophylls b and b? (561.2 ?g/g), pheophytins a and a? (31.7 ?g/g), hydroxychlorophyll b (26.5 ?g/g), hydroxychlorophylls a and a? (9.8 ?g/g), and chlorophyllides a and a? (0.35 ?g/g). A glass column containing 52 g of magnesium oxide?diatomaceous earth (1:3, w/w)could elute chlorophylls with 800 mL of acetone containing 50 percent ethanol at a flow rate of 10 mL/min. Some new chlorophyll derivatives including chlorophyllide b, pyropheophorbide b, hydroxypheophytin a, and hydroxypheophytin a? were generated during column chromatography but accompanied by a 63 percent loss in total chlorophylls. Thus, the possibility of chlorophyll fraction prepared from T. formosanum as a raw material for future production of functional food needs further investigation.
Keywords: TARAXACUM FORMOSANUM; CHLOROPHYLLS; HPLC-DAD-MS; COLUMN CHROMATOGRAPH